Mechanical properties of in situ modified graphene nanosheets‐reinforced polypropylene. Issue 7 (10th May 2022) - Dong, Haipeng; Liu, Minghui; Chen, Xianlei; Han, Guofang; Li, Liang; Lu, Fangfang; Zhu, Baikang; Tao, Hengcong
Abstract: Despite the great potential of graphene as a nanofiller, its inhomogeneous dispersion in polymers remains a key challenge for the effective reinforcement of polymer. Herein, we exfoliated worm graphite into graphene by in situ liquid‐phase exfoliation, and the graphene was coated on the surface of polypropylene (PP) pellets by stirring. Further, we examined several treatment conditions and graphene contents. When graphene was centrifuged at 1000 rpm and the extrusion temperature of the composite was 230°C, the composite achieved optimal overall performance with the addition of only 0.2 wt% graphene. Compared to those of pure PP, the yield strength, bending modulus, and impact strength of the composites increased by 8.71%, 18.32%, and 45.75%, respectively. The thermal conductivity is increased by 29.5%. X‐ray diffraction (XRD) and differential scanning calorimetry (DSC) showed that the PP sample exhibited a significant heterogeneous nucleation effect due to graphene addition, improving the crystallization temperature and crystallinity of the composites. Contact angle measurement and scanning electron microscopy (SEM) revealed that the surface energy of graphene and PP are close to each other, and the graphene was well‐dispersed in the PP matrix. Thus, this technique can optimize the processing properties and interface structure of graphene‐polymer nanocomposites. Abstract :